Biochemical heterogeneity, migration, and pre-fertilization release of mouse oocyte cortical granules - Liu, Min (BioMed Central, 2003)
BACKGROUND: Oocyte cortical granules are important in the fertilization of numerous species including mammals. Relatively little is known about the composition, migration, and pre-fertilization release of mammalian oocyte cortical granules. RESULTS: Results obtained with confocal scanning laser microscopy indicated that mouse oocytes have at least two populations of cortical granules, one that bound both the lectin LCA and the antibody ABL2 and one that bound only LCA. Both types of granules were synthesized at the same time during oocyte maturation suggesting that the ABL2 antigen is targeted to specific granules by a sorting sequence. The distribution of both populations of cortical granules was then studied during the germinal vesicle to metaphase II transition. As the oocytes entered metaphase I, the first cortical granule free domain, which was devoid of both populations of cortical granules, formed over the spindle. During first polar body extrusion, a subpopulation of LCA-binding granules became concentrated in the cleavage furrow and underwent exocytosis prior to fertilization. Granules that bound ABL2 were not exocytosed at this time. Much of the LCA-binding exudate from the release at the cleavage furrow was retained in the perivitelline space near the region of exocytosis and was deduced to contain at least three polypeptides with approximate molecular weights of 90, 62, and 56 kDa. A second cortical granule free domain developed following pre-fertilization exocytosis and subsequently continued to increase in area as both, LCA and LCA/ ABL2-binding granules near the spindle became redistributed toward the equator of the oocyte. The pre-fertilization release of cortical granules did not affect binding of sperm to the overlying zona pellucida. CONCLUSIONS: Our data show that mouse oocytes contain at least two populations of cortical granules and that a subset of LCA-binding cortical granules is released at a specific time (during extrusion of the first polar body) and place (around the cleavage furrow) prior to fertilization. The observations indicate that the functions of the cortical granules are more complex than previously realized and include events occurring prior to gamete membrane fusion.